2017
DOI: 10.1103/physreva.96.062708
|View full text |Cite
|
Sign up to set email alerts
|

Low-energy electron-impact dissociative excitation of molecular hydrogen and its isotopologues

Abstract: We apply the adiabatic nuclei convergent close-coupling method to electron-impact dissociative excitation of H2 in the low energy regime. Differential and integrated cross sections are presented for excitation of the b 3 Σ + u state, the primary pathway to dissociation of H2 at low energies. Agreement with experiment is satisfactory. Results are also presented for the isotopologues D2, T2, HD, HT, and DT, which show a pronounced isotopologue effect near threshold in both the differential and integrated cross s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 44 publications
2
31
0
Order By: Relevance
“…The account of nuclear motion becomes progressively more important as the incident electron energy becomes smaller. The adiabatic nuclei CCC approach [13] proved to be in good agreement with the experiment for energies below 13 eV. However, the agreement of the excitation DCS for the X 1 Σ g + → b 3 Σ u + transition in H 2 with theory was poor at incident energies above 13 eV with the largest, nearly a factor of two, discrepancies in some cases.…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…The account of nuclear motion becomes progressively more important as the incident electron energy becomes smaller. The adiabatic nuclei CCC approach [13] proved to be in good agreement with the experiment for energies below 13 eV. However, the agreement of the excitation DCS for the X 1 Σ g + → b 3 Σ u + transition in H 2 with theory was poor at incident energies above 13 eV with the largest, nearly a factor of two, discrepancies in some cases.…”
mentioning
confidence: 70%
“…At energies close to the excitation threshold the effects of nuclear motion have to be taken into account, and as incident electron energy increases inter-channel coupling plays a dominant role, both making theoretical treatments extremely difficult. While a large number of theoretical methods have been applied to calculation of the b 3 Σ u + excitation they are in significant disagreement with each other and with the recommended data (refer to Scarlett et al [13] for references and more detailed discussion). A recent breakthrough in the theoretical adaptation of the Convergent Close-Coupling (CCC) model of Bray and co-workers [14,15], which had been very successful for electron scattering from two-electron atoms, was applied to electron scattering from molecular hydrogen.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the FN approximation the excitation threshold of the b 3 Σ u + state is at 10.31 eV at the average internuclear distance of 1.448 a 0 adopted in the FN CCC calculations [17]. The adiabatic nuclei CCC approach [18] allows one to extend the theoretical technique to low excitation energies and proved to be in good agreement with the experiment for energies below 13 eV. The analysis of the CCC results has demonstrated that the nuclear motion effects are negligible above 13 eV verifying therefore the validity of the FN CCC results.…”
Section: Theoreticalmentioning
confidence: 99%
“…Similar to the experimental electron-H 2 data set, only fragmentary theoretical electron-impact cross section data were available, often with unqualified uncertainties and large discrepancies between various theoretical models and with experiment. This changed with the extension of the convergent close-coupling (CCC) method to electron collisions with molecules [13,14,15], and production of the first comprehensive theoretical data set of accurate e --H 2 cross sections [16,17,18]. A distinctive feature of the CCC cross section data set was an explicit demonstration of convergence and an estimate of an accuracy of better than 16% for most transitions.…”
mentioning
confidence: 99%